Working out of generalized dynamic model of cargo fixation with cargo pads jointly with flexible and thrust elements under the action spatial force system - Khabibulla TURANOV (Transport Problems, 2011)
The article gives an account of the results of working out a generalized dynamic model of fixation of cargo with pads jointly with flexible and thrust elements. Working out a generalized dynamic model of cargo fixation is rather a complicated problem not in the sense of solving differential equations systems but in the sense of presenting them as a complex mechanical system “cargo – pads – flexible elements – thrust bars”. Generalized dynamic model of cargo with pads observed that this model represents technology of joint work of flexible and thrust fastening means of cargo on rolling stock. In particular, on the basis of this model there can be obtained the technology models of joint work of flexible and elastic fastening means of cargo without pads of fastening flexible elements of cargo with pads without thrust bars and also flexible fastening elements of cargo without pads and thrust bars at asymmetrical and/or symmetrical allocation of cargo in the wagon. A specific feature (novelty feature) of the proposed dynamic model is inclusion into the model of both cargo pads and thrust bars which are nailed to the wagon floor close to the butt and lateral sides of cargo.